Associative learning in immature lacewings (Ceraeochrysa cubana). Issue 9 (4th August 2019) - de Oliveira, Cleber M.; Pallini, Angelo; Bernardo, Ana M.G.; Veiga, Valéria R.; de Brito, Luan A.R.; Venzon, Madelaine; de Lima, Eraldo R.; Janssen, Arne
Abstract: It is known that many social insects and arthropod predators and parasitoids can learn the association between a resource and volatile cues. Although there are various studies on the effect of experience in immature arthropods on behavior later in adult life, not much is known about the effects of such experiences on immature behavior. This was investigated here in the lacewing Ceraeochrysa cubana (Hagen) (Neuroptera: Chrysopidae). Whereas adults of this lacewing feed on plant‐provided food and honeydew, larvae are voracious polyphagous predators of several insect pests, and therefore important for biological control. Hence, studying the foraging behavior and the effects of learning in immatures of this species is important. We exposed immatures to the volatile methyl salicylate (MeSA), which was either associated with food or with the absence of food. Subsequently, their response to this volatile was tested in an olfactometer. Immatures that had experienced the association of MeSA with food were attracted to it and immatures that were exposed to MeSA during food deprivation were repelled. Subsequently, predator immatures that had experienced the association between MeSA and food were released on a plant without food and were found to use this volatile in locating patches with food. In contrast, larvae without such experience were found equally on food patches with and without the volatile. We conclude that these immature predators are capable of learning the association between volatiles and food, or the absence of food, and use this during foraging. Abstract : Whereas adults of the lacewing Ceraeochrysa cubana (Neuroptera: Chrysopidae) feed on plant‐provided food and honeydew, larvae are voracious polyphagous predators of several insect pests, and therefore important for biological control. We show that the immatures can learn the association between a volatile cue (methyl salicylate) and the presence or absence of food and that they use this learned association when searching for new patches with prey.